Psycho-Social aspects of infertility - R Kormi Nouri (JRI, 2000)
In this review article , the research conducted on the social and psychological aspects of infertility have been divided into two groups : The first group of studies believe that infertility may have psychological causes ( such as differences in personality and experiencing stress between infertile and non-infertile people). The second group of studies examine the psychological Consequences by both qualitative and quantitative methods. In general , the qualitative studies describe infertility as a devastating experience , especially for women. The qualitative studies try to measure the psychological consequences hypothesis by standard tests . The studies have shown that infertile subjects are different from non-infertile subjects with respect to psychological distress , stress , depression , self-steem , marital satisfaction and sexual satisfaction . However , in the quantitative studies compared to qualitative studies , there is more inconsistency in the literature . This may be due to both methodological problems (such as sampling , temporal dimension , control groups and cross-cultural variation ) and theoretical (conceptual ) problems . In the end , gender differences in infertility experience have been discussed and the review articles show that , in addition to psychololgical factors , we need to pay more attention to social and psychological aspects of infertility .
Keywords: Infertility, Psychological factors, quantitative & qualitative studies